2017
DOI: 10.1016/j.foodchem.2016.11.039
|View full text |Cite
|
Sign up to set email alerts
|

Cooking impact in color, pigments and volatile composition of grapevine leaves (Vitis vinifera L. var. Malvasia Fina and Touriga Franca)

Abstract: Grapevine leaves (Vitis vinifera L. var. Malvasia Fina and Touriga Franca) under culinary treatment (blanching and boiling at 60, 75 and 90min) were studied for their color, pigments and volatile fraction changes. Blanching and boiling caused a decrease in luminosity and a loss of green coloration in both varieties, while a yellow-brownish color arose. Significant correlations were established between the loss of green color (monochromatic variable a) and the total chlorophylls content. The main volatiles in f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 31 publications
0
24
0
Order By: Relevance
“…For semiquantitation purposes, relative concentrations (crel) of VOCs were calculated by the ratio of each individual peak area to the area of internal standard and converted to concentration equivalents based on the internal mass added [29].…”
Section: Wine Samplesmentioning
confidence: 99%
“…For semiquantitation purposes, relative concentrations (crel) of VOCs were calculated by the ratio of each individual peak area to the area of internal standard and converted to concentration equivalents based on the internal mass added [29].…”
Section: Wine Samplesmentioning
confidence: 99%
“…This might be due to an increased extraction over chlorophyll a over time, or to an increase in chlorophyll b degradation over time. Lima et al (2017) report that the thermostability of chlorophyll a is greater than that of chlorophyll b. This is however, in contrast with findings by Koca et al (2007), who found chlorophyll b to be more stable than chlorophyll a.…”
Section: Pigments In Rr Infusionsmentioning
confidence: 63%
“…Similar trends were observed for the different herbal masses used, the greatest extraction being achieved with brewing times between 2 and 5 min (p < 0.05), in agreement with the changes seen for the chromatic coordinates and color parameters. Beyond that time, pigment levels returned to their initial values, possibly due to the degradation caused by temperatures and oxygen exposure (Lima, Pereira, Baraldi, & Malheiro, 2017;Pumilia et al, 2014). Chlorophyll levels were higher than pheophytin levels, thus offering a plausible Figure 1.…”
Section: Pigments In Rr Infusionsmentioning
confidence: 99%
“…Polyphenols of grape by‐products such as leaves, seed, and skin are rich in bioactive compounds. Bioactive phytochemicals are found in grape leaves for consumers and industries for culinary purposes (Anđelković, Radovanović, Anđelković, & Radovanović, 2015; Babalık & Göktürk Baydar, 2019; Borai et al., 2017; Fenglin, Ruili, Bao, & Liang, 2004; Lima, Pereira, Baraldi, & Malheiro, 2017; Radovanovic, Andjelkovic, Radovanovic, Milenkovic‐Andjelkovic, & Dekic, 2015). Grapevine leaf composition is influenced by soil properties and the vegetative stage (Páscoa, 2018).…”
Section: Introductionmentioning
confidence: 99%